Different features of histopathological subtypes of pediatric focal cortical dysplasia - Krsek, Pavel; Maton, Bruno; Korman, Brandon; Pacheco-Jacome, Esperanza; Jayakar, Prasanna; Dunoyer, Catalina; Rey, Gustavo; Morrison, Glenn; Ragheb, John; Vinters, Harry V; Resnick, Trevor; Duchowny, Michael (Annals of neurology, 2008)
OBJECTIVE: Focal cortical dysplasia (FCD) is the most frequent pathological finding in pediatric epilepsy surgery patients. Several histopathological types of FCD are distinguished. The aim of the study was to define distinctive features of FCD subtypes. METHODS: We retrospectively reviewed clinical, electroencephalographic, magnetic resonance imaging, neuropsychological, and surgical variables, and seizure outcome data in 200 children. Cortical malformations were histopathologically confirmed in all patients, including mild malformation of cortical development type II (mMCD) in 36, FCD type Ia in 55, FCD type Ib in 39, FCD type IIa in 35, and FCD type IIb in 35 subjects. RESULTS: Perinatal risk factors were more frequent in mMCD/FCD type I than FCD type II. Children with FCD type IIb had more localized ictal electroencephalographic patterns and magnetic resonance imaging changes. Increased cortical thickness, abnormal gyral/sulcal patterns, gray/white matter junction blurring, and gray matter signal abnormality in fluid-attenuated inversion recovery and T2-weighted sequences occurred more often in FCD type II, were infrequent in FCD type I, and rare in mMCD. Lobar hypoplasia/atrophy was common in FCD type I. Hippocampal sclerosis was most frequent in FCD type I. Neuropsychological testing demonstrated no significant differences between the groups. There was a trend toward better surgical outcomes in FCD type II compared with FCD type I patients. INTERPRETATION: Different histopathological types of mMCD/FCD have distinct clinical and imaging characteristics. The ability to predict the subtype before surgery could influence surgical planning. Invasive electroencephalographic study should be considered when mMCD/FCD type I is expected based on noninvasive tests.
Keywords: Epilepsy; lidé; mladiství; magnetická rezonanční tomografie; Adult; Magnetic Resonance Imaging; Infant; Female; dítě; mozková kůra; Hippocampus; předoperační péče; Biopsy; Adolescent; Humans; Predictive Value of Tests; elektroencefalografie; předškolní dítě; Electroencephalography; Child, Preschool; mužské pohlaví; Malformations of Cortical Development; epilepsie; malformace mozkové kůry; Atrophy; Cerebral Cortex; biopsie; ženské pohlaví; Male; hipokampus; atrofie; Child; dospělí; prediktivní hodnota testů; Preoperative Care; kojenec